Case report: Management and long-term ophthalmic sequelae of monogenean ocular infestation in cownose rays (Rhinoptera bonasus) - Beatty, April; Gemensky-Metzler, Anne; Newbold, Georgina; Aplasca, Andrea C.; Seeley, Kathryn E. (Frontiers in Veterinary Science, 2024)
Monogenean ectoparasitic flatworm infestations, particularly in closely confined populations, can result in severe epizootic disease that is often devastating and occasionally fatal. This case series describes a population of cownose rays (Rhinoptera bonasus) (n=52) housed in an aquarium touch-tank exhibit that presented with severe ocular disease due to infestation with monogeneans, presumably Benedeniella posterocolpa of the Capsilidae family. The most severely affected individuals (n=9), including several cases with bilaterally ruptured corneas, underwent serial examinations prior to and following treatment with praziquantel, systemic antibiotics, and corticosteroids. The entire population underwent frequent therapeutic water changes with a scheduled decrease in salinity, increase in temperature, and a series of seven praziquantel tank treatments. At the last follow up examination (3.75 years), the most common ocular findings were corneal fibrosis (18/18 eyes; 100%), cataract formation (13/18 eyes; 72.2%), synechia (8/18 eyes; 44.4%), and dyscoria (5/18 eyes; 27.8%). Despite severe corneal disease, including corneal rupture, all examined eyes (18/18; 100%) showed remarkable corneal remodeling and a largely clear visual axis. There are very few reports describing corneal disease in aquarium housed elasmobranchs, and no reports describe ophthalmic implications of monogenean infestation in these animals. This further underscores the importance of this case series in demonstrating the capacity for healing of elasmobranch eyes and can provide further guidance regarding prognosis and treatment in cases of severe corneal disease.